Prior suggestive symptoms in one-third of patients consulting for a "first" demyelinating event. Issue 3 (19th November 2010) - Gout, O; Lebrun-Frenay, C; Labauge, P; Le Page, G E; Clavelou, P; Allouche, S; ,
Abstract : Objective: To evaluate the prevalence of prior inflammatory events in patients consulting for a first inflammatory neurological event and improve early diagnosis of multiple sclerosis. Methods: During the initial visit, the neurologist gave patients a self-administered questionnaire containing 72 questions regarding previous symptoms lasting >24 h. During the follow-up visit, the neurologist validated the symptoms and collected information about the current attack. Results: The cohort included 178 patients (74% women, mean age (SD) 33.7 (10.1) years). The main reason for the initial visit was visual disturbance and sensory troubles in limbs. Mean (SD) global Expanded Disability Status Scale score was 1.4 (1.1), 46% of brains MRIs were positive according to Barkhof–Tintoré criteria, 41% had abnormal white blood cell count in cerebrospinal fluid and 71% had immunoglobin G oligoclonal bands. Prior symptoms suggestive of demyelination were reported by 79 patients (44%), validated by the neurologist for 70% (55 patients) and identified only by the neurologist in four patients. Sequelae were observed in 14 patients with validated prior symptoms (26%). The self-administered questionnaire showed an overall sensitivity of 93% and specificity of 80% for identifying patients with prior symptoms suggestive of demyelination. Conclusion: A patient-administered questionnaire subsequently validated by the neurologist demonstrated that 33% of patients consulting for a first demyelinating event had prior symptoms suggestive of central nervous system demyelination that had gone unnoticed, and almost 70% had either sequelae of prior demyelination or McDonald criteria for dissemination in space. Such a questionnaire could be a useful tool for earlier diagnosis of multiple sclerosis.